The first of the viscoceuticals? A shear thickening gum induces gastric satiety in rats. Issue 1 (22nd December 2016) - Wee, M. S. M.; Lentle, R. G.; Goh, K. K. T.; Matia-Merino, L.
Abstract : We examined the effect of gavage of 4 ml of a viscous shear-thickening polysaccharide solution (15% w/w) extracted from the fronds of the mamaku tree fern ( Cythea medullaris ) in reducing appetite and delaying gastric emptying in twenty six Sprague Dawley rats. Abstract : We examined the effect of gavage of 4 ml of a viscous shear-thickening polysaccharide solution (15% w/w) extracted from the fronds of the mamaku tree fern ( Cythea medullaris ) in reducing appetite and delaying gastric emptying in twenty six Sprague Dawley rats. After two weeks habituation to a pelleted chow, the rats were gavaged on alternate days with either the mamaku extract or with the same volume of deionised water for a total of five times over a period of two weeks. The body mass and food intake of each rat were determined daily and the weights of their stomach contents determined on euthanasia two hours after the final gavage. The rats gavaged with the mamaku gum consumed significantly lower quantities of chow on the day of gavage. The weights of the stomach contents of rats two hours after gavage with mamaku extract were significantly greater than those following gavage with water. The failure of the rats dosed with mamaku to lose body weight likely resulted from the overall adverse effect of gavage on food intake, the limited numbers of doses of the gum and the rebound hyperphagia on days when the rats were not gavaged. Together the results indicate that gavage with mamaku gum delayed gastric emptying with respect to that of rats dosed with water and supressed appetite for 12–24 hours after dosage.